ITIL Lifecycle Essentials : Your Essential Guide for the ITIL Foundation Exam and Beyond. - Agutter, Claire (IT Governance Publishing, 2013)
This book doesn't just cover the information required to pass the foundation exam, but goes beyond this in providing practical guidance for when newly qualified practitioners enter the real-world. By addressing processes and concepts not covered in the syllabus, this book guides practitioners as they go beyond Foundation level. It features practical tips on using service management and, for each process, the author adds to the theory with lessons from her own real-world experience.